The Role of Fun at Work towards Job Satisfaction of Employee with Work Engagement as Mediator - Yan Ayu Permatasari; Asri Laksmi Riani (Universitas Sebelas Maret, 2018)
The purpose of this study is to examine the effect of fun at work on job satisfaction with work engagement as a mediation variable. Specifically, this study is intended is to find out the relationship between fun at work and work engagement, fun at work and work satisfaction, and fun at work and work satisfaction mediated by work engagement. Data were collected through surveys and conducted by distributing questionnaires to the company. The sampling technique used is a saturation sampling method, which all members of the population were used as the sample. The sample consisted of 65 respondents. The results of this study suggests that fun at work significantly affects work engagement. In addition, work involvement indirectly mediates between fun at work and job satisfaction. This phenomenon possibly can occur because a fun workplace can stimulate a good mood and excitement for employees in doing their job.